(untitled) (Journal of Tourism and Himalayan Adventures, 2023)
The tourism sector is essential to economic growth and has the capacity to stimulate the economy. The aim of this paper to assess the relationship between tourism industry and its economic growth. The gross domestic product (GDP) indicates the economic growth and tourism industry development relates to tourist arrivals, length of stay, and gross foreign exchange earnings from tourism. This study is grounded on secondary data collected from the Economic Survey of Nepal and the Nepal Tourism Statistics from 2000 to 2021. The study finds short and long-term causality between tourism industry and economic growth. The tourism development indicators include arrivals of tourist, length of stay, and gross foreign exchange from tourism. The unidirectional causality of economic growth to the length of stay of tourists and tourism to gross foreign exchange earnings were observed in the study. Adequate government strategies for the tourism sector can accelerate economic growth. The policymakers should give adequate attention to diversifying the tourism services, improving infrastructure, encouraging local communities, promoting sustainable tourism, enhancing marketing efforts, and promoting collaborations between the public, commercial sectors and local communities to support tourism industry for the sustained in Nepal.